Analisis Pengaruh Atribut Produk, Bauran Promosi, dan Kualitas Pelayanan terhadap Keputusan Pembelian Produk Merchandise - Khasanah, Imroatul; Pamujo, Novian Yuga (Jurnal Ilmiah Aset, 2011)
This research was motivated by the increasing number of business merchandise in major cities in Indonesia. The one is Kedai Digital 7 Semarang, a business unit engaged in different fields of creative production in particular areas of merchandise and graphic design. The data were collected through questionnaire method of 100 respondents of Kedai Digital 7 in Semarang, which was obtained by using non-probability sampling technique. Then, we analyzed the data obtained by using multiple regressionanalysis. This analysis included validity and reliability, classical assumption test, multiple regression analysis, hypothesis testing by T-test and F-test, and analysis of determination coefficien (R2). Hypothesis trial by T-test showed that the three examined independent variables (product attributes variable, promotional mix, and service quality) were proven having positive and significant impact toward the dependent variables of purchasing decisions. Then, from F-test could be seen that the three independent variables were proper to exmine the dependent variables of purchasing decision. Adjusted R Square of 0.555 indicated that 55.5 % of the purchasing decision variables could be explained by the three independent variables in the regression equation. While the rest 44.5 % could be explained by other variables outside of the three variables used in this study.